Cultural adaptation and feasibility of a multimodal cognitive intervention for older adults with Mild Cognitive Impairment - Karim, Mani Abdul; Jonnadula, Venkatachalam (YCAB Publisher, 2025)
Background:Non-pharmacological interventions have shown considerable promise in alleviating the symptoms of Mild Cognitive Impairment (MCI). Among these, a multicomponent or multimodal approach that integrates cognitive and compensatory strategies has demonstrated effectiveness in slowing cognitive decline. Objectives:This study aimed to evaluate the feasibility of the Indian Adapted Motivationally Enhanced Compensatory Cognitive Training for Mild Cognitive Impairment (IAME-CCT-MCI) intervention for older adults. Methods:This preliminary study focused on assessing the content validity of the IAME-CCT-MCI intervention. A panel of field experts, comprising clinical psychologists and rehabilitation specialists (N=7), evaluated the intervention modules based on their relevance, effectiveness, and appropriateness for the target population. Results:Expert evaluations indicated a high level of agreement regarding the intervention’s suitability. The modules were rated as highly relevant to the target population (M=3.87), effective in addressing cognitive targets (M=3.84), and appropriate for older adults with MCI (M=3.87). Conclusions:These findings support the feasibility and relevance of the IAME-CCT-MCI intervention for older adults with MCI. Further research is needed to evaluate the usability and efficacy of this intervention in larger and more diverse samples. Keywords:feasibility; IAME-CCT-MCI intervention; older adults; mild cognitive impairment